2018
DOI: 10.1017/s0022149x18000494
|View full text |Cite
|
Sign up to set email alerts
|

Helminth community and host dynamics in northern bobwhites from the Rolling Plains Ecoregion, U.S.A.

Abstract: One hundred and sixty-one northern bobwhites (Colinus virginianus; hereafter 'bobwhite') were examined from the Rolling Plains ecoregion of Texas and western Oklahoma from 2011 to 2013. Complete necropsies yielded 13 species, of which two are new host (Gongylonema phasianella) and region (Eucoleus contortus) records and three (Dispharynx nasuta, Tetrameres pattersoni and Oxyspirura petrowi) are known to cause morbidity and mortality. Of the species found, Aulonocephalus pennula commonly occurred, Oxyspirura pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…While there are numerous recent studies on eyeworm and caecal worm prevalence in the Rolling Plains (Dunham et al, 2016b; Henry et al, 2017; Brym et al, 2018; Bruno et al, 2018), this is the first study to analyze and predict eyeworm and caecal worm intensity and reproduction in bobwhites based on climatic factors. By analyzing predictive statistics on available temperature and precipitation data, this study reveals the potential of climate to influence both eyeworms and caecal worms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…While there are numerous recent studies on eyeworm and caecal worm prevalence in the Rolling Plains (Dunham et al, 2016b; Henry et al, 2017; Brym et al, 2018; Bruno et al, 2018), this is the first study to analyze and predict eyeworm and caecal worm intensity and reproduction in bobwhites based on climatic factors. By analyzing predictive statistics on available temperature and precipitation data, this study reveals the potential of climate to influence both eyeworms and caecal worms.…”
Section: Discussionmentioning
confidence: 97%
“…Yet, Henry et al (2017) reported 100% prevalence of eyeworms in bobwhite captured in March 2017 from Mitchell County, Texas. In contrast, caecal worm prevalence has remained at 90%–100% in the Rolling Plains over the past several years, though intensity can vary by individual bobwhite (Dunham et al, 2017b; Brym et al, 2018; Bruno et al, 2018). These differences in prevalence could be explained by variances in temperature and precipitation as environmental conditions may vary from county to county in the Rolling Plains (Modala et al, 2017), potentially impacting intensities of both parasites.…”
Section: Discussionmentioning
confidence: 99%
“…pennula and O . petrowi , contributing to the declines of local bobwhite populations ( Bruno, 2014 ; Dunham et al, 2014a ; Bruno et al, 2019a ). Evidence exists of parasites like Loa and Thelazia callipaeda , which are closely related to O .…”
Section: Using the Woe Framework To Investigate The Role Of Parasitesmentioning
confidence: 99%
“…In the Rolling Plains, there have been extensive studies investigating the effects of O. petrowi on bobwhite and surveys have identified it to be highly prevalent throughout the ecoregion [7, 12]. For instance, Dunham et al [13] found 58.7% of adult bobwhite across 29 counties in the Rolling Plains to be infected with O. petrowi , while others have found some areas with a prevalence of 100% [10, 11].…”
Section: Introductionmentioning
confidence: 99%